TH/U ZONATION IN ZIRCON DERIVED FROM EVAPORATION ANALYSIS: A MODEL AND ITS IMPLICATIONS - Klotzli U.S. (My University, 1999)
Zircon evaporation analyses often exhibit the existence of spatial extraneous variations in 208Pb/206Pb compared to 207Pb/206Pb as revealed by increasing evaporation temperature and duration of analysis. As 208Pb solely stems from the decay of 232Th, variations are interpreted to directly reflect changing Th/U ratios within different zircon domains which are probed at different evaporation temperatures and evaporation duration. Such strongly varying Th/U is interpreted as reflecting the magmatic growth zonation in the zircon crystal. Constant Th/U over several evaporation steps is interpreted as being characteristic for homogeneous zircon domains which probably originate from zircon recrystallisation or growth during a metamorphic event. Stepwise evaporation of zircon crystals and the monitoring of Th/U ratios thus provide some means to decipher the internal structure of the analysed zircon and therefore allows some conclusions about magmatic vs. recrystallised or newly grown metamorphic origin to be drawn.
Keywords: GEOCHRONOLOGY; ZIRCON EVAPORATION ANALYSIS; ZONATION; CRYSTAL CHEMISTRY